Keanekaragaman dan Pemanfaatan Makroalga di Perairan Pulau Rumadan Dullah Utara Kota Tual - Silaban, Rosita; Josephs Souisa, Fabian Novy; Dobo, Johny; Watubun, Sarifa; Sudirjo, Fien; Thedora Silubun, Dortje (Rekayasa, 2024)
Macroalgae serve as the foundation of the aquatic food chain, significantly contributing to primary productivity in coastal waters, acting as indicators of aquatic ecosystem health, and can be utilized as food, traditional medicine, and industrial raw materials. This research aims to analyze density, biomass, ecological index, and vitamin C content. Macroalgae samples were collected using the square line transect method. The macroalgae found on Rumadan Island consist of 35 species classified into 3 divisions, 3 classes, 10 orders, 18 families, and 20 genera. The group of green algae (Chlorophyta) consists of 12 species, the group of brown algae (Ochrophyta) consists of 7 species, and the group of red algae (Rhodophyta) consists of 16 species. The environmental parameters on Rumadan Island can be tolerated for the survival of macroalgae. The highest density of the species Ulva lactuca is 9.3 ind/m2, while the lowest density is of the species Halimeda micronesica at 0.9 ind/m2. The highest biomass is found in the species Galaxaura fastigiata (73.3 gr/m2) and Ulva lactuca (68 gr/m2), while the lowest is in Chaetomorpa crassa (1.8 gr/m2). A diversity index of 2.87 is categorized as moderate, a uniformity index of 0.807 is categorized as high, and dominance of 0.097 is categorized as low/stable. The vitamin C content in several species of macroalgae on Rumadan Island is quite high, ranging from 1,232 to 5,280 mg/g.